2022
DOI: 10.1186/s12871-022-01811-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dexmedetomidine on cardiac electrophysiology in patients undergoing general anesthesia during perioperative period: a randomized controlled trial

Abstract: Background Dexmedetomidine has controversial influence on cardiac electrophysiology. The aim of this study was to explore the effects of dexmedetomidine on perioperative cardiac electrophysiology in patients undergoing general anesthesia. Methods Eighty-one patients were randomly divided into four groups: groups D1, D2, D3 receiving dexmedetomidine 1, 1, 0.5 μg/kg over 10 min and 1, 0.5, 0.5 μg/kg/h continuous infusion respectively, and control gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…28 The mechanism involved may be related to the high dose of Dex reducing norepinephrine release, inhibiting atrioventricular node and sinoatrial node functions, and exciting the vagus nerve. 29,30 Our results revealed that the incidence of bradycardia was significantly higher in Group D than in Group C, whereas use of atropine was not required, implying that no intervention was needed in most cases of bradycardia induced by low-dose Dex. It has been reported that hypotension is another common adverse effect of Dex.…”
Section: Discussionmentioning
confidence: 66%
“…28 The mechanism involved may be related to the high dose of Dex reducing norepinephrine release, inhibiting atrioventricular node and sinoatrial node functions, and exciting the vagus nerve. 29,30 Our results revealed that the incidence of bradycardia was significantly higher in Group D than in Group C, whereas use of atropine was not required, implying that no intervention was needed in most cases of bradycardia induced by low-dose Dex. It has been reported that hypotension is another common adverse effect of Dex.…”
Section: Discussionmentioning
confidence: 66%
“…Like corrected QT interval (QTc), iCEBc is also corrected by heart rate. As the marker of assessing risk of arrhythmia, it is widely used in the clinical research, but there is still no evidence of an association between iCEBc and its prognosis (11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%